CP-159 Direct acting antivirals (DAAS) for the treatment of HCV infection in HIV/HCV coinfected patients: A clinical experience. (14th February 2016) - Corinaldesi, G; Sentinelli, R; Guglielmi, S; Orsetti, E; Castelletti, S; Marigliano, A; Riva, A; Tontini, C; Costantini, A
Abstract : Background: HIV/hepatitis C virus (HCV) coinfection has an unfavourable influence on the natural history of HCV, resulting in an increased rate of progression to cirrhosis, HCC and end stage liver disease. 1 Although direct acting antivirals (DAAs) have proven to be effective in eradicating HCV infection in coinfected individuals, 2, 3 few data on cost effectiveness in clinical practice are available to date. Purpose: This prospective study aims to assess efficacy and costs of DAAs in an outpatient population of HIV/HCV coinfected subjects. Material and methods: A database for DAA prescription monitoring was created, including information on the overall cost of the anti-HCV regimen for each patient. Patients were treated according to the local prescription regulations. Virologic response to DAAs was assessed at weeks 4, 12 and 24 after treatment initiation. Additional clinical and laboratory data were obtained from the medical records. Results: 35 subjects were studied (males 80%, mean age 51 years), 23 undergoing a 12 week treatment course and 12 a 24 week course. Prior to initiation, 74% of patients had HIV plasma viral load below the detection limit. 80% changed at least one HIV medication to minimise the risk of drug-drug interactions; eventually, 71% switched to an integrase inhibitor based regimen. 87% of patients undergoing a 12 week DAA regimen had HCV genotype 1 infection whereas 67% of patients on a 24 week regimen had genotype 3. An interferon free regimen was chosen for 91% of patients. Ribavirin was used in combination with DAAs in 57% of subjects. Preferred combinations were simeprevir/sofosbuvir for the treatment of genotype 1 and sofosbuvir/ribavirin or daclatasvir/sofosbuvir for genotype 3. Other combinations were paritaprevir/dasabuvir/ombitasvir/ritonavir and ledipasvir/sofosbuvir. 55% of patients showed undetectable HCV viraemia at week 4 and 86% at week 12. To date, 22 patients have completed the full treatment course (19 patients 12 weeks, 3 patients 24 weeks), all showing undetectable HCV viraemia. Among these, 23% experienced mild side effects, all related to ribavirin co-administration (anaemia, fatigue). Mean treatment cost was approximately 55 000€ per patient. Conclusion: This prospective study shows the effectiveness and safety of DAA therapy in HIV/HCV coinfected individuals in the clinical setting, despite the high cost. Data collection on sustained virologic response after treatment discontinuation is still ongoing. References and/or Acknowledgements: Lo Re V, et al. Ann Intern Med 2014;160:369 Sulkowski MS, et al. JAMA 2014;312:353 Osinusi A, et al. J Hepatol 2014;60:67 No conflict of interest.